Training for Village-Owned Enterprises in Managing Tourism in Mopaano Village, Buton Regency - Wijaya, Andy Arya Maulana; Sari, Putri Mawang; Al Haris, Ahmad Dahlan; Restiawati, Restiawati; Nastia, Nastia (Universitas Nahdlatul Ulama Surabaya, 2025)
Village-Owned Enterprises have an important role in managing village tourist attractions. Tourism development through village tourism is one of the efforts to support village economic growth. The problem faced by partners is the lack of development insight in the tourism sector, which is an obstacle to the development of the Mopaano Village tourism business due to a lack of training and management knowledge in developing tourist attractions. This training is to improve skills in managing tourism. This training was carried out by delivering material about tourism as a strength for the village economy and tourism promotion to increase tourist visits. Community Service Activities are carried out in Mopaano Village. The Mopaano Village tourist attraction is a village asset that needs to be empowered and developed with all its uniqueness and attractiveness to attract tourist visits to the village tourist location. With training methods carried out in community service, to introduce good promotional methods that suit the needs of Mopaano Village. This training is aimed at BUMDes and Karang Taruna in Mopaano Village. This training takes the form of promotional design and the use of information technology in digital marketing so that it accommodates the need to improve village tourism promotion so that it can be a solution to overcome partner problems. The Service Team also provides training in designing visiting packages when traveling to Mopaano Village and provides several souvenir plans to remind tourists who have visited Mopaano Village.